Physico-chemical Parameterization and Determination of Effect of Tributaries on Enhancement of Pollutants in Bagmati River - Adhikari, Mandira Pradhananga; Neupane, Madhav Raj; Kafle, Madan (Journal of Nepal Chemical Society, 2019)
Water quality parameterization is a great concern because chemical contaminants and microbiological impurities including pathogenic bacteria may pose a health risk and unfit for its domestic use. Alkalinity, pH, conductivity, chlorine demand, turbidity, and ammonia were measured to characterize the water quality of the Bagmati River. The effect of tributaries on Bagmati River was determined by sampling water from five different sites such as Pashupati (B-1), Shankhamul (B-2), Kupondol (B-1), Balkhu (B-4), and Jalbinayek (B-5) sites. The water samples B-2, B-3, B-4 and B-5 were less turbid but black in color while water sample B-1 was more turbid but grey in color. The pH of water samples ranged from 6.7 to 7.3. The alkalinity, conductivity and chlorine demand were 60 ppm, 95.7 µs and, 5.44 ppm, respectively for B-1 sample and increased almost continuously from B-2 to B-5 sample. The alkalinity was 360 ppm, conductivity was 862 µs and chlorine demand was 23.7 ppm for the last sample (B-5). The concentration of ammonia in the B-1 sample was only 0.0625 ppm whereas it was 3.32 ppm in the B-5 sample. The enhancement of chlorine demand and concentration of ammonia attributed that tributary and local effluent loaded extremely high levels of pollutants into the Bagmati River which might include pathogenic microorganisms. The random chance of some parameters like pH, conductivity, ammonia, turbidity along the Bagmati River indicates the impacts of different tributaries on Bagmati River. The chorine demand showed a positive correlation with conductivity, alkalinity and ammonia while the negative correlation with turbidity. This revealed that the conductive alkaline pollutants consumed more chlorine than colloidal particles. From the study it is considered that the Bagmati River water contains natural as well as anthropogenic pollutants which is extremely hazardous not only to the people using river water but also for the living organism rely on the river.